Ca2+- and ROS-dependent induction of heat resistance of wheat seedlings by exogenous melatonin - Taraban, D.A.; Karpets, Yu.V.; Yastreb, T.O.; Dyachenko, A.I.; Kolupaev, Yu.E. (Reports of the National Academy of Sciences of Ukraine, 2022)
Melatonin (N-acetyl-5-methoxytryptamine) is now considered an important regulatory molecule not only for animals but also for plants. Its importance isfound out in the adaptation of plants to the action of stressors of different nature, due, in particular, to enhance the functioning of the antioxidant system. However, the role of signal mediators in the implementation of the stress-protective effect of melatonin remains poorly understood. The aim of the study was to establish the possible participation of reactive oxygen species (ROS) and calcium ions in the process of inducing heat resistance of wheat seedlings by exogenous melatonin. 24-hour treatment of 4-day etiolated seedlings with melatonin in concentrations in the range of 0.1–10 μM caused a significant increase in their survival after the damaging heating in a water thermostat (45 °C, 10 min). Incubation of seedlings in melatonin solution caused a transient increase of hydrogen peroxide content in the roots with a maximum after 1 h, but at the end of incubation (24 h) there was a decrease in the amount of H2O2 compared to control. The melatonininduced effect of increasing of hydrogen peroxide content in seedling roots was eliminated by the H2O2 scavenger dimethylthiourea (DMTU) and the NADPH oxidase inhibitor imidazole. Also, this effect was not revealed in the presence of calcium antagonists – EGTA (extracellular calcium chelator) and neomycin (inhibitor of calcium influx into cytosol from intracellular compartments), which indicates the dependence of melatonin-induced ROS formation on calcium homeostasis. Treatment of seedlings with antioxidant DMTU, NADPH oxidase inhibitor imidazole, calcium antagonists EGTA and neomycin also almost completely eliminated the positive effect of melatonin on seedling survival after damaging heating. It is concluded that ROS and calcium are involved as signaling mediators in the process of increasing the heat resistance of wheat seedlings by melatonin.